Graduate entrepreneur analytical reports (GEAR) using data warehouse model: A case study at CEDI, Universiti Utara Malaysia (UUM) - Abu Bakar, Muhamad Shahbani (2011)
Business Intelligence (BI) system using Data Warehouse (DW) technology is one of the important strategic management approaches in the organizations today.BI combines architectures, databases, analytical tools, and methodologies to enable interactive information access focused on analytical reports.Analytical reports, which affect the long-term direction of the entire company, are typically made by top managers. Decisions making in an organization is very difficult, especially if the organization has poor quality data and limited information.The management in the organization always depended on the past experiences and their instincts when making a decision making without support from the factual information. DW is a technology enable to integrate and transform enterprise data for strategic decision making.The organization, which is, responsible to manage entrepreneur activities need an analytical report for strategic decision making.This paper is focused how to design and develop Graduate Entrepreneur Analytical Reports called GEAR by using a DW model in Cooperative and Entrepreneur Development Institute (CEDI), Universiti Utara Malaysia (UUM) as a case study. This system has been tested through the system user feedback by using Computer System Usability Questionnaire (CSUQ), which measures satisfaction and consumer usability.